Pengaruh Regulasi Emosi terhadap Harga Diri Siswa Sekolah Menengah Atas di Yogyakarta - Muarifah, Alif; Fauziah, Mufied; Saputra, Wahyu Nanda Eka; Da Costa, Augusto (Jurnal Kajian Bimbingan dan Konseling, 2019)
Self-esteem is an important element for students to support their development optimally. However, students performed various problems related to the students’ self-esteem level. For instance, students posted their activities and problems on social media. One variable affected self-esteem was students’ emotional control. This study aimed to identify the effect of emotional control on students’ self-esteem. This study involved 612 students as sample who were randomly selected in the Special Region of Yogyakarta. Data analysis technique in this research was regression analysis. Results indicated that there was a significant effect of emotional control on students’ self-esteem. This study recommended a counseling service to increase students’ self-esteem by involving emotional control variable.